2003
DOI: 10.1111/1540-5893.3703004
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Reversal as an Explanation of Lower Court Compliance

Abstract: Lower courts in the United States are generally responsive to specific precedents and trends in the decisionmaking of their judicial superiors. In this article, we ask why. We test one popular explanation—that compliance can be attributed to judges' fear of having their decisions reversed—through an analysis of search and seizure cases decided in the U.S. Courts of Appeals between 1961 and 1990. Since the Supreme Court cannot reverse a decision unless it agrees to review it, we ask whether circuit judges are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 41 publications
0
64
1
Order By: Relevance
“…Given that reversal occurs so rarely, it is small wonder that studies have difficulty identifying any effect that the prospect of reversal might have (Klein & Hume 2003, Songer et al 2003.…”
Section: Reversal Aversionmentioning
confidence: 99%
“…Given that reversal occurs so rarely, it is small wonder that studies have difficulty identifying any effect that the prospect of reversal might have (Klein & Hume 2003, Songer et al 2003.…”
Section: Reversal Aversionmentioning
confidence: 99%
“…Research on the appeals courts, however, has found little evidence of reversal aversion (Klein and Hume 2003;Cross 2007; Songer, Humpries and Sarver 2003). With respect to the district 4 district judges want to avoid reversal, and appellate judges decide cases on the basis of political preferences, then district judges will decide cases on the basis of the political preferences of appellate judges.…”
Section: Introductionmentioning
confidence: 99%
“…That is, even for random selection, there will be a nonnegligible degree of measurement error, which should be taken into account in drawing inferences from such compliance studies. It is worth noting that the degree of misclassification is roughly equal to the noncompliance level found by Klein and Hume (2003) and is perhaps greater than the overall amount of noncompliance that previous studies have found to exist among lower federal courts (e.g., Gruhl 1980;Songer & Sheehan 1990). …”
Section: Percent Misclassificationsmentioning
confidence: 73%
“…The third set of bars in Figure 1 shows that a majority of liberal decisions-61 percent-are measured as noncompliant, compared to 14 percent of conservative decisions. Although one might seek to explain this discrepancy by assuming that liberal panels are simply more likely to disobey the Supreme Court, breaking Note: Percentages are based on data analyzed in Klein and Hume (2003). The first set of bars shows that the direction of case outcomes varies little by panel ideology.…”
Section: B Compliance and The Noncompliance Puzzlementioning
confidence: 99%